Thermoelastic finite element model updating with application to monumental buildings. (22nd November 2019) - Ceravolo, Rosario; De Lucia, Giulia; Miraglia, Gaetano; Pecorelli, Marica L.
Abstract: A reliable and predictive model of an existing structure entails the use of model updating techniques, which are usually performed on the basis of operational modal analysis campaigns. In this paper, a new model calibration strategy is proposed that adopts a multiphysics approach to exploit data collected by both static and dynamic monitoring systems. More specifically, mechanical and temperature data are assimilated into the model through a thermoelastic updating. The proposed scheme is validated with numerical simulations and applied on the Sanctuary of Vicoforte, a complex historical building that is subjected to both static and dynamic monitoring.